Obesity, Ethnicity, and Risk of Critical Care, Mechanical Ventilation, and Mortality in Patients Admitted to Hospital with COVID‐19: Analysis of the ISARIC CCP‐UK Cohort. Issue 7 (14th May 2021) - Yates, Thomas; Zaccardi, Francesco; Islam, Nazrul; Razieh, Cameron; Gillies, Clare L.; Lawson, Claire A.; Chudasama, Yogini; Rowlands, Alex; Davies, Melanie J.; Docherty, Annemarie B.; Openshaw, Peter J. M.; Baillie, J. Kenneth; et al.
Abstract : Objective: The aim of this study was to investigate the association of obesity with in‐hospital coronavirus disease 2019 (COVID‐19) outcomes in different ethnic groups. Methods: Patients admitted to hospital with COVID‐19 in the United Kingdom through the Clinical Characterisation Protocol UK (CCP‐UK) developed by the International Severe Acute Respiratory and emerging Infections Consortium (ISARIC) were included from February 6 to October 12, 2020. Ethnicity was classified as White, South Asian, Black, and other minority ethnic groups. Outcomes were admission to critical care, mechanical ventilation, and in‐hospital mortality, adjusted for age, sex, and chronic diseases. Results: Of the participants included, 54, 254 (age = 76 years; 45.0% women) were White, 3, 728 (57 years; 41.1% women) were South Asian, 2, 523 (58 years; 44.9% women) were Black, and 5, 427 (61 years; 40.8% women) were other ethnicities. Obesity was associated with all outcomes in all ethnic groups, with associations strongest for black ethnicities. When stratified by ethnicity and obesity status, the odds ratios for admission to critical care, mechanical ventilation, and mortality in black ethnicities with obesity were 3.91 (3.13‐4.88), 5.03 (3.94‐6.63), and 1.93 (1.49‐2.51), respectively, compared with White ethnicities without obesity. Conclusions: Obesity was associated with an elevated risk of in‐hospital COVID‐19 outcomes in all ethnic groups, with associations strongest in Black ethnicities.